Remigiusz Szauer, Between the Need for Sensations and the Persistence of Attitudes. Religiousness and Morality of High School and University Students in the Koszalin-Kołobrzeg Diocese. A Sociological Study, Publishing House: WWS, Warsaw 2019, pp. 481 - Choczyński, Marcin (Uniwersyteckie Czasopismo Socjologiczne, 2019)
The work of fr. Remigiusz Szauer represents another theoretical and empirical publication in the rather rich reserve of Polish studies of religion and religiosity of selected social categories. One can recall here works that have relatively recently been published (Mariański 2018; Štefanák 2018 – work on Slovak youth; Zaręba, Zarzecki 2018) and at the same time constitute a continuation of the research tradition undertaken by distinguished authors in the field of sociology of religion, e.g. Władysław Piwowarski and Janusz Mariański. Suffice to say that the entire sphere of the Polish sociology of religion in relation to this specific dimension, i.e. the study of juvenile religiosity, is characterized by a large number of both conducted studies and publications presenting the results of analyses. These are mostly studies that refer to a statistical, quantitative picture of the character of young people’s beliefs, change trends and the essence of expressed participation in a worship (Zaręba 2003; Mariański 2008; Zaręba 2008; Zaręba 2012). Comprehensive studies on the religiosity of young people also allow us to capture specific historical and generational dimensions of social life, their basic configurations.